2018
DOI: 10.15520/ijnd.v8i09.2290
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Quality of Life among Students at Technical Institute of Nursing, Mansoura University, Egypt

Abstract: Internet addiction prevails among students who uncontrollably immerse themselves in it as a way of escaping from their challenges and stressors which may negatively affect their quality of life. Aim of this study: to investigate the prevalence of internet addiction and its influence on quality of life among students of the technical institute of nursing, Mansoura University. Methods a descriptive cross-sectional research design was used to achieve the aim of this study. The present study was conducted at the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…In a study conducted on nursing students, Ragheb et al (2018) found that inappropriate use of the internet adversely affects the students’ quality of life. They believed that excessive use of the internet was a way for the students to run away from the pressures of real-life or parental conflicts [ 46 ], which agrees with the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted on nursing students, Ragheb et al (2018) found that inappropriate use of the internet adversely affects the students’ quality of life. They believed that excessive use of the internet was a way for the students to run away from the pressures of real-life or parental conflicts [ 46 ], which agrees with the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…In general, "Internet Addiction (IA)" is defined as excessive use of the Internet accompanied by withdrawal, tolerance, and negative repercussions (Chung, J. Lee& H. Lee, 2019). IA is considered a public health problem around the world particularly among adolescents (Ragheb et al, 2018). The present study was conducted to assess the prevalence of IA among adolescents using a representative sample of middle and high school adolescents in Mansoura city.…”
Section: Discussionmentioning
confidence: 99%
“…Community health nurses have important role in investigating public health problems to formulate appropriate educational and nursing interventions that improves adolescents' overall physical, social and psychological wellbeing (Ragheb, El-Boraie, Shohda& Ibrahim, 2018). So that investigating the level of internet addiction internet addiction among adolescents, is important as a high-risk group.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have found that internet use is signi cantly associated with reduced communication with friends and social networks, which causes further loneliness and a decrease in some aspects of quality of life [45]. In a study conducted on nursing students, Ragheb et al (2018) found that inappropriate use of the internet adversely affects the students' quality of life. They believed that excessive use of the internet was a way for the students to run away from the pressures of real life or parental con icts (46), which agrees with the present ndings.…”
Section: Discussionmentioning
confidence: 99%